Fiscal Rules : Useful Policy Framework or Unnecessary Ornament? - Kopits, George (Washington, D.C. : International Monetary Fund, 2001)
With the primary objective of conferring credibility on macroeconomic policies, an increasing number of advanced and emerging market economies have adopted various forms of fiscal rules (mainly balanced-budget requirements and debt limits). In contrast to previous fiscal rules, many of which lacked transparency, recently introduced rules have the potential of serving as a useful depoliticized policy framework, and over time, can contribute to stability and growth. To this end, they need to be well designed and supported by an appropriate institutional infrastructure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet